Prenatal Air Pollution Exposure and Early Cardiovascular Phenotypes in Young Adults. - Carrie V Breton (PLoS ONE, 2016)
Exposure to ambient air pollutants increases risk for adverse cardiovascular health outcomes in adults. We aimed to evaluate the contribution of prenatal air pollutant exposure to cardiovascular health, which has not been thoroughly evaluated. The Testing Responses on Youth (TROY) study consists of 768 college students recruited from the University of Southern California in 2007-2009. Participants attended one study visit during which blood pressure, heart rate and carotid artery arterial stiffness (CAS) and carotid artery intima-media thickness (CIMT) were assessed. Prenatal residential addresses were geocoded and used to assign prenatal and postnatal air pollutant exposure estimates using the U.S. Environmental Protection Agency's Air Quality System (AQS) database. The associations between CAS, CIMT and air pollutants were assessed using linear regression analysis. Prenatal PM10 and PM2.5 exposures were associated with increased CAS. For example, a 2 SD increase in prenatal PM2.5 was associated with CAS indices, including a 5% increase (β = 1.05, 95% CI 1.00-1.10) in carotid stiffness index beta, a 5% increase (β = 1.05, 95% CI 1.01-1.10) in Young's elastic modulus and a 5% decrease (β = 0.95, 95% CI 0.91-0.99) in distensibility. Mutually adjusted models of pre- and postnatal PM2.5 further suggested the prenatal exposure was most relevant exposure period for CAS. No associations were observed for CIMT. In conclusion, prenatal exposure to elevated air pollutants may increase carotid arterial stiffness in a young adult population of college students. Efforts aimed at limiting prenatal exposures are important public health goals.